Prevalence and geographic distribution of haemophilia in Costa Rica - Arroyo, J.; Salazar-Sánchez, L.; Jiménez-Cruz, G.; Chaverri, P.; Arrieta-Bolaños, E.; Morera, B. (Hämostaseologie, 2010)
Haemophilia is the most frequent hereditary haemorrhagic illness and it is due to the deficiency of coagulation factors VIII (haemophilia A, HA) or IX (haemophilia B, HB).The prevalence of this disease varies according to the country, those having better survival rates having also higher prevalences. Specifically in Costa Rica, there are around 130 HA and 30 HB families. This study reports the prevalence and a spatial distribution analysis of both types of the disease in this country. The prevalence of haemophilia in this country is 7 cases per 100 000 men, for HA it is 6 cases per 100 000 and for HB it is 1 case per 100 000 male inhabitants. The prevalence of this disease is low when compared with other populations. This low prevalence could be due to the many patients that have died because of infection with human immunodeficiency virus during the 1980s. The prevalence of haemophilia in Costa Rica is almost one half of that present in developed countries. Nevertheless, the ratio between HA and HB follows world tendency: 5 : 1. In this study, nationwide geographical distribution maps were drawn in order to visualize the origin of severe cases and how this influences the pattern of distribution for both types of haemophilia. By means of these maps, it was possible to state that there is no association between the sites of maximum prevalence of mutated alleles and ethnicity. With this study, haemophilia prevalence distribution maps can be used to improve efforts for the establishment of hemophilia clinics or specialized health centers in those areas which hold the highest prevalences in this country. Also, this knowledge can be applied to improve treatment skills and offer the possibility of developing focused genetic counseling for these populations.
Keywords: Haemophilia; geographic distribution; spatial analysis; Costa Rica